ANALISIS KESEHATAN BANK PADA BANK MUAMALAT INDONESIA DAN BANK SYARIAH MANDIRI DENGAN METODE CAMEL - Yuyun Wahyuni (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2020)
This research analyzed financial reports of BMI (Bank Muamalat Indonesia) and BSM (Bank Syariah Mandiri) in 2005 to 2013 through CAMEL method. The purposes of this research are to know the health level of Bank Muamalat Indonesia & Bank Syariah Mandiri and to understand the differences characteristic of parameters that control its health level. Some parameters are used to analyzed, they are CAR, NPM, ROA, BOPO & LDR. Interesting phenomenone are found through this research BMI is categorized health bank when evaluated from CAR, NPM, ROA & BOPO. Otherwhile, LDR of BMI does not indicate that bank is healthy the evaluation of CAR, NPM, ROA, BOPO & LDR in BSM indicates that BSM is healthy bank, but NPM & ROA parameters show the condition of BSM is unhealth. Statistically, NPM and BOPO ratio of both are signoficantly different, while other parameters (CAR, ROA & LDR) are in the same level /condition